AP versus PA positioning in lumbar spine computed radiography: Image quality and individual organ doses. Issue 2 (May 2015) - Davey, Enda; England, Andrew
Abstract Purpose Radiological imaging examinations must be optimised in order to ensure that the radiation dose is kept as low as reasonably possible (ALARP). The aim of this study was to compare anteroposterior (AP) and posteroanterior (PA) projections of the lumbar spine, at various kVp increments, in order to establish optimum parameters. Methods An anthropomorphic phantom was imaged in both the AP/PA projections and at various kVp increments. Acquisitions were undertaken using a Wolverson Acroma X-ray unit and processed using an Agfa computed radiography (CR) unit. The entrance surface dose was recorded and converted to effective and organ doses using PCXMC 2.0 software. Five observers were then asked to evaluate the images, using a two-alternative force choice (2AFC) approach and a scale based on EC guidelines. Results The PA projection lowered the mean effective dose by 19.8% and also the mean absorbed dose to the stomach (70.4%), colon (61.1%), remainder tissues (33.2%), ovaries (7.3%) and testes (15.9%). However, this was at the expense of slightly inferior image quality, not statistically significant. For AP projections, a higher kVp is a further option for dose reduction. Conclusion Dose optimisation requires the production of an image that is acceptable for the purpose intended. Based on ALARP, and when taking into consideration the dose reductions in this study, it may now be time to routinely use PA projections when imaging the lumbar spine. The use of a higher kVp should also be considered as an option but would be more useful for AP projections.